Perspektif Hukum Islam Tentang Memangkas Rambut Bagi Wanita Dengan Meniru Model Artis Terkenal - Syaripudin, Enceng Iip; Nurjanah, Aji (STAI Al Musaddadiyah Garut, 2024)
In modern times, many people are adopting trends from Western cultures. A notable phenomenon is women emulating the hairstyles of famous South Korean celebrities. This admiration often leads to many women displaying their hairstyles without covering their aurat (parts of the body that should be covered according to Islamic teachings). The research questions addressed in this study are: How does Islam view women cutting their hair in styles mimicking those of celebrities? What actions do Muslims take to preserve their religion and lineage in relation to the trend of copying celebrity hairstyles? How does Islamic law perceive salon services in the context of this trend? The objectives of this study are: to explore the Islamic perspective on women cutting their hair to resemble celebrity hairstyles; to examine the measures taken by Muslims to safeguard their religious values concerning the phenomenon of adopting celebrity hairstyles; and to understand the Islamic legal stance on salon services that cater to this trend. This research employs a qualitative methodology using library research methods. The approach involves document analysis. The conclusions drawn from this study include: Women cutting their hair in styles similar to those of celebrities may not necessarily constitute tasyabbuh (imitation of non-Muslims), depending on the context and application; there are efforts by Muslims to uphold their religious principles in response to the trend of mimicking celebrity hairstyles; and salon services are deemed permissible in Islam as they provide benefits for women, provided they adhere to Islamic guidelines. Keywords : Islamic Law; Haircut; Celebrity Hairstyles